Prosthetic Contact Lens Combined with Strabismus Surgery : Confronting Psychosocial Prejudice in Anomalous and Misaligned Eyes: Poster Presentation - Case Report - Resident - PRISCILLA DWIANGGITA; Ariesanti Tri Handayani; Ni Made Ayu Surasmiati (Majalah Oftalmologi Indonesia, 2023)
Introduction : Patients with defects in the cornea such as abnormal size, opacities as well as misalignment of the eyes may feel inferior about their physical appearance. Such patients will benefit from prosthetic contact lenses (CL) and strabismus surgery to restore anatomical appearance. The majority of patients also seek strabismus surgery for both cosmetic and psychosocial reasons along with decreased levels of anxiety and depression. Our goal not merely cosmetic, but also improving psychosocial health and quality of life. Case Illustration : We reported a 14-year-old male with complaints of white spot on his left eye and squint since birth. On ophthalmology examination, we found 45 degree esotropia with BCVA 6/6 in the right eye and 1/300 in the left eye. Corneal diameter was 10 mm and 9 mm on the right and left eye, respectively. He was diagnosed with right eye posterior embryotoxon, left eye corneal dystrophy, microcornea on both eye, congenital esotropia and deprivative amblyopia. He had developed low self-esteem due to his eyes. To enhance his appearance, left eye lateral rectus resection and medial rectus recession with adjustable suture was done to align the eye. Afterwards, brown-tinted soft contact lens with power -0.50 D, diameter 14,2 mm, and base curve 8,5 mm was given to disguise the corneal opacities and microcornea. Patient felt very satisfied with the result. Discussion : Conclusion : Prosthetic contact lens combined with strabismus surgery provides satisfactory cosmetic and psychosocial benefit with minimal complications. As clinicians, functional, cosmetic and psychosocial indications must be considered for a comprehensive management.